JAMBI COMMUNITY TRADITION AS THE INSPIRATION OF TEXTILE ART WORKS - Adelya, Dina (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2019)
This study project raises the issue of Jambi people's cultural tradition with the rapid development of technology, enabling a change of cultural values. Jambi cultural traditions can be seen from the cultural elements of living equipment systems include traditional traditional dress and economic system covering the livehood of batik and hunting by the Suku Anak Dalam. Then the problem is the author embodied into the form of textile art with visualization of the imagination of the author using textiles, yarn and beads. The work made through the process of searching the source of ideas and references by visiting the museum of Negeri Jambi and Seberang Jambi City, make, move the sket to the fabric, sew patchwork in the end by adding details using threads and beads. The resulting work has a variety of sizes 100 cm x 150 cm and 50 cm x 75 cm. the author produces textile artwork that has a texture impression that can not only be seen but also can be felt with hand touch.